2018
DOI: 10.1186/s12891-018-1934-9
|View full text |Cite
|
Sign up to set email alerts
|

Manual therapy in the treatment of patients with hemophilia B and inhibitor

Abstract: BackgroundThe main clinical manifestations of hemophilia are muscle and joint bleeding. Recurrent bleeding leads to a degenerative process known as hemophilic arthropathy. The development of inhibitors (antibodies against FVIII/FIX concentrates) is the main complication in the treatment of hemophilia. The objective was to assess the safety and efficacy of manual therapy treatment in a patient with hemophilia and inhibitor.Case presentationA 26-year-old patient with hemophilia B and inhibitor received physiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…This is because one of the physiological effects of MT is pain inhibition that may be caused not only by the neural pathways, but also by the mechanical effect on the tissues and the body fluids, and the psychosomatic effect. Our results were consistent with MT studies in HA 17‐21 . Heijnen and De Kleijn 17 suggested that both interventions were effective in reducing pain and increasing functional level.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is because one of the physiological effects of MT is pain inhibition that may be caused not only by the neural pathways, but also by the mechanical effect on the tissues and the body fluids, and the psychosomatic effect. Our results were consistent with MT studies in HA 17‐21 . Heijnen and De Kleijn 17 suggested that both interventions were effective in reducing pain and increasing functional level.…”
Section: Discussionsupporting
confidence: 91%
“…The majorities of studies were with validity and reliability, and mostly, the effectiveness of HJHS was not evaluated. Cuesta Barriuso and Trelles‐Martinez 21 reported in their case study with inhibitor that MT decreased the index‐HJHS of the right ankle from 10 to 8 points (%20↓) and the left ankle from 9 to 8 points (% 11.1↓), but the index‐HJHS of the knee did not change. On the contrary, the decreases in index‐HJHS in both joints were found to be significant in MTG.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some studies have shown that manual therapy has safe and convenient techniques for haemophilia although previously stated as theoretically contraindication. Significant decrease in frequency of haemarthrosis of elbow joint with manual therapy & exercises was seen, and this result was found compatible with literature 4,8,27 . It has been reported that manual therapy stimulates joint mechanoreceptors, 28 releases soft tissues by reducing muscle‐reflexogenic activity and provides reflex inhibition by oscillatory movements during mobilizations 29 .…”
Section: Discussionsupporting
confidence: 86%
“…This scale, with scores ranging from 0 (no pain) to 10 points (maximum pain experienced by the patient), has been widely used in the assessment of joint pain in patients with hemophilia. 14,15 This evaluation was carried out by asking patients to define their perception of ankle joint pain, under load-bearing and non-load-bearing conditions.…”
Section: Methodsmentioning
confidence: 99%